Acute Endurance Exercise Induces Nuclear p53 Abundance in Human Skeletal Muscle - Tachtsis, Bill; Smiles, William J.; Lane, Steven C.; Hawley, John A.; Camera, Donny M. (Frontiers in Physiology, 2016)
PURPOSE: The tumour suppressor protein p53 may have regulatory roles in exercise response-adaptation processes such as mitochondrial biogenesis and autophagy, although its cellular location largely governs its biological role. We investigated the subcellular localization of p53 and selected signaling targets in human skeletal muscle following a single bout of endurance exercise. METHODS: Sixteen, untrained individuals were pair-matched for aerobic capacity (VO2peak) and allocated to either an exercise (EX, n = 8) or control (CON, n = 8) group. After a resting muscle biopsy, EX performed 60 min continuous cycling at ~70% of VO2peak during which time CON subjects rested. A further biopsy was obtained from both groups 3 h post exercise (EX) or 4 h after the first biopsy (CON). RESULTS: Nuclear p53 increased after 3 h recovery with EX only (~48%, p<0.05) but was unchanged in the mitochondrial or cytoplasmic fractions in either group. Autophagy protein 5 (Atg-5) decreased in the mitochondrial protein fraction 3 h post EX (~69%, P<0.05) but remained unchanged in CON. There was an increase in cytoplasmic levels of the mitophagy marker PINK1 following 3 h of rest in CON only (~23%, P<0.05). There were no changes in mitochondrial, nuclear or cytoplasmic levels of PGC-1α post-exercise in either group. CONCLUSIONS: The selective increase in nuclear p53 abundance following endurance exercise suggests a potential pro-autophagy response to remove damaged proteins and organelles prior to initiating mitochondrial biogenesis and remodelling responses in untrained individuals.